Atlas of the History of Modern Science 1500-2020 - Brobjer, Thomas H. author. aut Link
XV, 227 p. 211 illus., 8 illus. in color.
Keywords: This Atlas of the History of Modern Science functions as a textbook to help the student, by means of diagrams and flowcharts, to better understand both science and the history of science. It thus also aids the reader to better grasp the modern worldview. Students can, at a glance, see the grand picture and orient him- or herself among different traditions and thinkers, and better organize and structure information about the history of science and the scientific developments. This atlas is an invaluable textbook to every student of science, of the history of science, as well as for others seeking to understand our modern Weltanschauung, and how we have arrived at it.